Pelatihan Teknik Parafase dalam Pengutipan Literatur pada Mahasiswa Pendidikan Sejarah Universitas Pattimura - Maysuri, Tama; Harnisa, Susi; Putro, Rendy Wahyu Satriyo (Universitas Pattimura, 2024)
Community service activities in the form of Training and Coaching on Paraphrasing Techniques in Citing Literary Works for History Education Students of Pattimura University aim to improve paraphrasing skills and students' understanding of the ethics of citing academic literary works. The problem often faced by students is the difficulty in paraphrasing correctly, which results in the risk of plagiarism. This training is carried out in four stages, namely initial survey, counseling, practical guidance, and monitoring and evaluation. The initial survey helps identify students' basic level of understanding of paraphrasing techniques. The counseling and interactive discussion stages provide theoretical insights into academic ethics and paraphrasing techniques. Through practical guidance, students gain direct experience and feedback that improves the quality of their paraphrasing. Continuous monitoring through academic assignments and online discussion forums is also provided to monitor the development of students' paraphrasing skills. The results of the training show a significant increase in paraphrasing skills and students' awareness of the importance of citing literature ethically and effectively. Thus, this activity contributes to building a responsible academic culture at Pattimura University, especially in developing students' academic literacy skills in the field of history.